2012
DOI: 10.1016/j.acap.2011.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Parental Report and Electronic Health Record Documentation as Measures of Diet and Physical Activity Counseling

Abstract: Objective To determine whether parental reports and electronic health record documentation of physician counseling on nutrition and physical activity reflect actual counseling provided. Methods Participants were parents of 198 children 2–12 years of age seen in a primary care pediatric clinic at an academic medical center for well child care and their 38 physicians. Parents completed a post-visit questionnaire to reported discussions on weight, nutrition and physical activity that occurred during the visit. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 25 publications
2
18
0
Order By: Relevance
“…The study team's previous research demonstrates that assessing clinician documentation may underestimate the true frequency of these behaviors, particularly for outcomes related to discussion. 29 The team also was unable to classify risk factor assessment and counseling for visits during which risk factor assessment occurred but the presence of a risk factor was unclear and counseling was not delivered, although this accounted for a very small number of observations-specifically, 5 for nutrition, 15 for physical activity, and 15 for screen time. Although the study team accounted for correlation related to clustering by physician, the team was unable to account for varying depth of relationship between parents and providers.…”
Section: Discussionmentioning
confidence: 99%
“…The study team's previous research demonstrates that assessing clinician documentation may underestimate the true frequency of these behaviors, particularly for outcomes related to discussion. 29 The team also was unable to classify risk factor assessment and counseling for visits during which risk factor assessment occurred but the presence of a risk factor was unclear and counseling was not delivered, although this accounted for a very small number of observations-specifically, 5 for nutrition, 15 for physical activity, and 15 for screen time. Although the study team accounted for correlation related to clustering by physician, the team was unable to account for varying depth of relationship between parents and providers.…”
Section: Discussionmentioning
confidence: 99%
“…Recall accuracy and bias, particularly for questions about issues generally believed to reflect good parenting, may affect the results. However, the questionnaire items used to construct measures of anticipatory guidance were adapted from an existing instrument, 27 and the consistent differences between mothers of children with obesity versus mothers of children with healthy weight and overweight indicates that recall bias could not be account for the results.…”
Section: Discussionmentioning
confidence: 99%
“…Anticipatory guidance measures were adapted from Shaikh et al 27 These measures included recalling if the health care provider discussed child’s weight; food related issues of what the mother should feed her child, feeding children fruits and vegetables, limiting outside food from restaurants, eating breakfast, having family meals together, and not serving soda and sweetened beverages; and activity related issues of time watching television and videos, playing video games or using computer, and amount of physical activity or exercise. A total food guidance measure was based on the total number of food-related issues the mother recalled (0–6); a total activity guidance measure was based on the total number of activity related issues the mother recalled (0–3).…”
Section: Methodsmentioning
confidence: 99%
“…We used parental report of provider counseling behaviors rather than directly measuring counseling behaviors. Though parental report of provider behavior has been shown to be a valid proxy 17 , recall bias may still have affected the results, resulting in underreporting by some participants, overreporting by other participants, or variable reporting of different topics. We assessed counts of prevention-focused conversations.…”
Section: Discussionmentioning
confidence: 99%
“…Studies employing parental report vary depending on the length of time since the clinic visit, visit type, and the child's age 16 . Despite these limitations of using parental report, a recent study demonstrated that parental recall is a time- efficient and cost-effective method with higher sensitivity than medical record review and good convergent validity with audio-recorded visits 17 .…”
Section: Introductionmentioning
confidence: 99%